Value of Functionalized Superparamagnetic Iron Oxide Nanoparticles in the Diagnosis and Treatment of Acute Temporal Lobe Epilepsy on MRI. (27th January 2016) - Fu, Tingting; Kong, Qingxia; Sheng, Huaqiang; Gao, Lingyun
Abstract : Purpose. Although active targeting of drugs using a magnetic-targeted drug delivery system (MTDS) with superparamagnetic iron oxide nanoparticles (SPIONs) is a very effective treatment approach for tumors and other illnesses, successful results of drug-resistant temporal lobe epilepsy (TLE) are unprecedented. A hallmark in the neuropathology of TLE is brain inflammation, in particular the activation of interleukin-1 β (IL-1 β ) induced by activated glial cells, which has been considered a new mechanistic target for treatment. The purpose of this study was to determine the feasibility of the functionalized SPIONs with anti-IL-1 β monoclonal antibody (mAb) attached to render MRI diagnoses and simultaneously provide targeted therapy with the neutralization of IL-1 β overexpressed in epileptogenic zone of an acute rat model of TLE. Experimental Design. The anti-IL-1 β mAb-SPIONs were studied in vivo versus plain SPIONs and saline. Lithium-chloride pilocarpine-induced TLE models (n = 60 ) were followed by Western blot, Perl's iron staining, Nissl staining, and immunofluorescent double-label staining after MRI examination. Results. The magnetic anti-IL-1 β mAb-SPION administered intravenously, which crossed the BBB and was concentrated in the astrocytes and neurons in epileptogenic tissues, rendered these tissues visible on MRI and simultaneously delivered anti-IL-1 β mAb to the epileptogenic focus. Conclusions. Our study provides the first evidence that the novel approach enhanced accumulation and the therapeutic effect of anti-IL-1 β mAb by MTDS using SPIONs.